Dihydropteridine reductase activity in dried blood spots: effects of aging and senile dementia of the Alzheimer type. Issue 2 (February 1986) - Jeeps, C M; Silcox, A; Lloyd, B; Clayton, B E
Abstract : Dihydropteridine reductase (EC 1.6.99.7) (DHPR) activity was measured in blood spots from 50 neonates, 52 healthy adults aged 30-62 years, and 21 elderly controls aged 67-97 years, as well as 32 demented patients of whom 25 had senile dementia of the Alzheimer type. Enzyme activity was stable for seven days at 4 degrees C and for at least 14 days at -20 degrees C. No important difference was found between the DHPR activity of venous and capillary blood. DHPR activity was considerably lower in the healthy adult group compared with neonates and the elderly group, and there was no sex difference at any age. The erythrocyte DHPR activity of patients with senile dementia of the Alzheimer type was similar to that of elderly controls. This result differs from that previously reported for leucocytes.